Reorienting Critical Geographies of Global Development: A Conversation with Han Cheng, Patricia Daley, Ruben Gonzalez-Vicente, Diana Vela-Almeida, and Joseph Awetori Yaro - Pepa, Mariasole; Mohan, Giles; Cheng, Han; Daley, Patricia; Gonzalez-Vicente, Ruben; Vela-Almeida, Diana; Awetori Yaro, Joseph (ACME, 2025)
This roundtable on reorienting critical geographies of global development was organized in response to “The Critical Geography Conversations: ACME’s 20+ Year Anniversary”. It brought together scholars from diverse backgrounds—including Han Cheng, Patricia Daley, Jospeh Yaro, Ruben Gonzalez-Vicente, and Diana Vela-Almeida—to reflect on significant shifts in global development geographies, such as the rise of the Global South, the consolidation of Brazil, Russia, India, China, and South Africa (BRICS), especially China’s role, and the urgency to question established spatial categories. The conversation created a space for collective reflection on the possibilities and challenges of reshaping how we teach, research, and engage with the world. In an era where unlearning and rethinking are vital to envisioning alternative futures, this dialogue emphasized the importance of forging new ways of being, feeling, and thinking about development and geography.